H3K27me3 demethylases regulate in vitro chondrogenesis and chondrocyte activity in osteoarthritis. - Yapp, C; Carr, A; Price, A; Oppermann, U; Snelling, S (BioMed Central, 2016)
Background Epigenetic changes (i.e., chromatin modifications) occur during chondrogenesis and in osteoarthritis (OA). We investigated the effect of H3K27me3 demethylase inhibition on chondrogenesis and assessed its utility in cartilage tissue engineering and in understanding cartilage destruction in OA. Methods We used a high-content screen to assess the effect of epigenetic modifying compounds on collagen output during chondrogenesis of monolayer human mesenchymal stem cells (MSCs). The impact of GSK-J4 on gene expression, glycosaminoglycan output and collagen formation during differentiation of MSCs into cartilage discs was investigated. Expression of lysine (K)-specific demethylase 6A (UTX) and Jumonji domain-containing 3 (JMJD3), the HEK27Me3 demethylases targeted by GSK-J4, was measured in damaged and undamaged cartilage from patients with OA. The impact of GSK-J4 on ex vivo cartilage destruction and expression of OA-related genes in human articular chondrocytes (HACs) was assessed. H3K27Me3 demethylase regulation of transforming growth factor (TGF)-β-induced gene expression was measured in MSCs and HACs Results Treatment of chondrogenic MSCs with the H3K27me3 demethylase inhibitor GSK-J4, which targets JMJD3 and UTX, inhibited collagen output; expression of chondrogenic genes, includingSOX9andCOL2A1; and disrupted glycosaminoglycan and collagen synthesis.JMJD3but notUTXexpression was increased during chondrogenesis and in damaged OA cartilage, suggesting a predominant role of JMJD3 in chondrogenesis and OA. GSK-J4 prevented ex vivo cartilage destruction and expression of the OA-related genesMMP13andPTGS2.TGF-βis a key regulator of chondrogenesis and articular cartilage homeostasis, and TGF-β-induced gene expression was inhibited by GSK-J4 treatment of both chondrogenic MSCs and HACs. Conclusions Overall, we show that H3K27me3 demethylases modulate chondrogenesis and that enhancing this activity may improve production of tissue-engineered cartilage. In contrast, targeted inhibition of H3K27me3 demethylases could provide a novel approach in OA therapeutics.